A Versatile Strategy to Main Chain Sulfur/Selenium‐Functionalized Polycarbonates by Macro‐Ring Closure of Diols and Subsequent Ring‐Opening Polymerization. Issue 4 (27th December 2017) - Wei, Chao; Zhang, Yan; Yan, Bingkun; Du, Zhengzhen; Lang, Meidong
Abstract: Herein, a new class of main chain functionalized aliphatic polycarbonates with sulfur/selenium functional groups on the backbone is reported. Sulfur/selenium‐containing cyclic carbonate monomers (MR ) are designed and synthesized by enzyme‐catalyzed intermolecular macro‐ring closure of related diols. The proposed synthetic strategy is tolerant of other functionalities such as N‐substituted groups. The ring opening polymerization (ROP) of MR occurs readily as a versatile route to generate a new family of main chain sulfur/selenium substituted aliphatic polycarbonates (PR) with predictable molecular weights (MW), narrow molecular‐weight distribution and controlled copolymer composition. The resultant polymers can be oxidized and/or reduced by treatment with hydrogen peroxide (H2 O2 ) or dithiothreitol (DTT), highlighting their potential for applications in the stimuli‐responsive field and inflammation/cancer targeting. With these desirable results, it is revealed that this versatile technique can provide a broad‐reaching method to the next generation of innovative materials, especially, well‐defined biodegradable chalcogen‐based main chain functional biomaterials. Abstract : A versatile and facile synthetic strategy is reported for the preparation of well‐defined main‐chain‐functionalized degradable polymers by the enzyme‐catalyzed macro‐ring closure of functional diol and subsequent ring‐opening polymerization. Using this method, main chain sulfur/selenium‐substituted polycarbonates are synthesized for the first time with excellent redox responsiveness. Moreover, this approach could be broadened to other functional diols, effectively expanding the range of accessible main chain functional polymers.